English for Occupational Purposes: A Needs Analysis of Fitness Club Cashier in Bali - Abenader Rendy Mesang; Ni Made Diana Erfiani; Yohanes Octovianus Lesu Awololon (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2026)
In today’s globalized service industry, English has become an essential tool for communicating with international clients. Nevertheless, many fitness staff still experience difficulties in using English effectively within professional workplace interactions. This study aims to analyze the English language needs of cashier staff at Macan Gading Fitness Club, Bali, from an applied linguistics perspective. This study employs a qualitative descriptive method using observation, interviews, and documentation to collect data from three cashier participants. The study focuses on identifying the types of English skills, communicative situations, and workplace expressions required in daily interactions, assessed across four dimensions: pronunciation accuracy, vocabulary range, confidence, and fluency. The findings reveal that speaking and listening are the most essential English skills required by cashier staff across four target communicative situations: greeting and welcoming members, explaining facilities and membership packages, answering member inquiries, and handling complaints. Through the ESP needs analysis framework of Hutchinson and Waters (1987), the study identifies staff necessities in these workplace interactions, highlights significant lacks in vocabulary, grammatical accuracy, confidence, and fluency, and reveals participants’ wants for context-specific English training, particularly in workplace vocabulary, spontaneous interaction, and complaint-handling communication. This study contributes to the field of English for Specific Purposes (ESP) by providing empirical evidence and practical insights into language training for fitness industry staff in tourist-dense regions.